Establishing a duration standard for the calculation of session rating of perceived exertion in NCAA division I men`s soccer - Pustina, A. A.; Sato, K.; Liu, C.; Kavanaugh, A. A.; Sams, M. L.; Liu, J.; Uptmore, K. D.; Stone, M. H. (Journal of Trainology, 2017)
Objectives: The purpose of this study was to determine the best predictor of training and/or match load using session RPE. Design and Methods: 20 NCAA DI male soccer players participated in the study during the 2014 and 2015 competitive seasons. Players completed 15.20 ± 1.05 matches for a total of 304 individual data points and 29.90 ± 1.89. training sessions for a total of 598 individual data points. GPS variables (total distance, High-intensity running distance, and Player load) were analyzed with session RPE using Pearson product-moment correlations. To evaluate various methods of session RPE, "match duration" was recorded using eight different definitions: total match duration including warm-up and half-time, total match duration and warm-up, total match duration and half-time, total match duration only, minutes played including warm-up and half-time, minutes played and warm-up, minutes played and half-time, and minutes played only. A one-way ANOVA with repeated measures was used to determine if differences existed between the eight session RPE calculations. Results: Results from the ANOVA showed that all session RPE measures were significantly different from one another (P < 0.05). Very large correlations were reported between session RPE calculated using minutes played and total distance (0.81), while session RPE calculated using match duration showed less magnitude (0.57). Conclusions: Minutes played should be used to calculate session RPE as it was found to most closely reflect the actual workloads incurred during competitive matches.